2017
DOI: 10.1002/joc.5286
|View full text |Cite
|
Sign up to set email alerts
|

Lightning activity associated with precipitation and CAPE over Bangladesh

Abstract: Satellite‐derived lightning data for 17 years (1998–2014) were used to evaluate the relation between environmental factors and lightning activity over the Bangladesh landmass. Time series convective available potential energy (CAPE) data were extracted from ERA‐40 reanalysis data while total and convective rainfalls were obtained from Tropical Rainfall Measuring Mission's monthly products. In addition, the product of CAPE and precipitation was computed and used as an additional variable. Three timescales – mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
29
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 86 publications
5
29
1
Order By: Relevance
“…Time averaging often reduces noise and enhances statistical relations, but, in this case, time averaging serves to highlight deficiencies of CP during the warm season. Dewan et al () also found low correlation of annual numbers of total flashes over Bangladesh with CP, but found a statistically significant relation with CAPE, which is not present here (not shown). The correlation of annual CONUS CP with counts of positive CG flashes is considerably larger ( r = 0.8; Figure ), although that correlation drops to 0.52 when the largest annual value (2016) is removed.…”
Section: Resultscontrasting
confidence: 64%
See 1 more Smart Citation
“…Time averaging often reduces noise and enhances statistical relations, but, in this case, time averaging serves to highlight deficiencies of CP during the warm season. Dewan et al () also found low correlation of annual numbers of total flashes over Bangladesh with CP, but found a statistically significant relation with CAPE, which is not present here (not shown). The correlation of annual CONUS CP with counts of positive CG flashes is considerably larger ( r = 0.8; Figure ), although that correlation drops to 0.52 when the largest annual value (2016) is removed.…”
Section: Resultscontrasting
confidence: 64%
“…Furthermore, the use of spatially complete reanalysis data allows us to form the product of collocated CAPE and precipitation rate (denoted CP) on a spatially resolved grid and to examine regional features of the association of the CAPE‐precipitation product with CG lightning flash counts. A similar study of lightning over Bangladesh, where lightning is an especially dangerous hazard Dewan et al (), found that the CP was more strongly associated with total lightning flash counts during the pre‐monsoon season than during the monsoon season (Dewan et al, ).…”
Section: Introductionmentioning
confidence: 94%
“…CAPE represents the potential buoyancy of idealized rising air parcel and thus is a measure of the instability of atmosphere. The relationship between CAPE and lightning activity has been found in many other regions over the world such as India, Southeast Asia, and Bangladesh Pawar et al, 2012;Siingh et al, 2013;Murugavel et al, 2014;Dewan et al, 2018). Pawar et al (2012) studied the relationship between CAPE and lightning activity over central India during summer monsoons.…”
Section: Methodsmentioning
confidence: 99%
“…Lightning is also one of the important sources of nitrogen oxides in the atmosphere, and thus the occurrence of lightning has a significant influence on global atmospheric chemistry (Schumann and Huntrieser, 2007;Murray, 2016;Tost, 2017). Therefore, research on the response of lightning to various meteorological factors and climate change remains an important research topic (Reeve and Toumi, 1999;Xiong et al, 2006;Romps et al, 2014;Kotroni and Lagouvardos, 2016;Dewan et al, 2018;Finney et al, 2018). Therefore, research on the response of lightning to various meteorological factors and climate change remains an important research topic (Reeve and Toumi, 1999;Xiong et al, 2006;Romps et al, 2014;Kotroni and Lagouvardos, 2016;Dewan et al, 2018;Finney et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The CAPE model uses a threshold of Convective Available Potential Energy (CAPE) to assess the risk of lightning. Assessing the level of CAPE which is well understood to be reflective of environments favorable to the development of lightning, 22,24,56 the CAPE model would be a more objective comparative scheme. Similar to the E-FIELD model, the corresponding threshold for each subset and lead time is defined in a way that the CSI is maximized.…”
Section: Machine Learning Model Performance For Long-range Lightning mentioning
confidence: 99%